Zinc Oxide Nanoconjugates against Brain-Eating Amoebae - Ruqaiyyah Siddiqui; Anania Boghossian; Noor Akbar; Tooba Jabri; Zara Aslam; Muhammad Raza Shah; Ahmad M. Alharbi; Hasan Alfahemi; Naveed Ahmed Khan (MDPI AG, 2022)
Naegleria fowleri and Balamuthia mandrillaris are opportunistic protists, responsible for fatal central nervous system infections such as primary amoebic meningoencephalitis (PAM) and granulomatous amoebic encephalitis (GAE) with mortality rates higher than 90%. Threatening a rise in cases is the increase in temperature due to global warming. No effective treatment is currently available. Herein, nanotechnology was used to conjugate Zinc oxide with Ampicillin, Ceftrixon, Naringin, Amphotericin B, and Quericitin, and the amoebicidal activity and host cell cytotoxicity of these resulting compounds were investigated. The compounds ZnO-CD-AMPi, ZnO-CD-CFT, ZnO-CD-Nar, ZnO-CD-AMB, and ZnO-CD-QT were found to reduce N. fowleri viability to 35.5%, 39.6%, 52.0%, 50.8%, 35.9%, and 69.9%, respectively, and B. mandrillaris viability to 40.9%, 48.2%, 51.6%, 43.8%, and 62.4%, respectively, when compared with their corresponding controls. Furthermore, the compounds reduced N. fowleri-mediated and B. mandrillaris-mediated host cell death significantly. Additionally, the compounds showed limited cytotoxicity against human cells; cell toxicity was 35.5%, 36.4%, 30.9%, 36.6%, and 35.6%, respectively, for the compounds ZnO-CD-AMPi, ZnO-CD-CFT, ZnO-CD-Nar, ZnO-CD-AMB, and ZnO-CD-QT. Furthermore, the minimum inhibitory concentrations to inhibit amoeba growth by 50% were determined for N. fowleri and B. mandrillaris. The MIC50 for N. fowleri were determined to be 69.52 µg/mL, 82.05 µg/mL, 88.16 µg/mL, 95.61 µg/mL, and 85.69 µg/mL, respectively; the MIC50 of the compounds for B. mandrillaris were determined to be 113.9 µg/mL, 102.3 µg/mL, 106.9 µg/mL, 146.4 µg/mL, and 129.6 µg/mL, respectively. Translational research to further develop therapies based on these compounds is urgently warranted, given the lack of effective therapies currently available against these devastating infections.